Altering visual feedback during reaching: no mitigating effect on pain for individuals with complex regional pain syndrome, but visuomotor adaptation is preserved - Dagenais, Marion; Sutter, Chloé; Brun, Clémentine; Pinard, Anne Marie; Roy, Jean-Sébastien; Mercier, Catherine (Frontiers in Human Neuroscience, 2025)
IntroductionComplex regional pain syndrome (CRPS) is often associated with pain-related fear of movement, and virtual reality has been proposed as a potential rehabilitation intervention to overcome this issue. Therefore, this cross-sectional study aimed to test whether altering the visual feedback (VF) on movement could mitigate pain and promote movement.MethodsFifteen participants with upper-limb CRPS and 15 age- and gender-matched pain-free participants undertook a target reaching task in the Kinarm exoskeleton, with two VF conditions being tested (Per Exposure: GREATER or SMALLER VF; two separate sessions), preceded and followed by reaching movements without VF (Pre-/Post-Exposure). Proprioception was assessed with a Limb Position Sense task, and a Movement Accuracy outcome was derived from the Pre-Exposure reaching movements.ResultsContrary to our hypothesis, pain intensity was not influenced by VF conditions but increased over Time (p < 0.001). Analyses performed on kinematics data showed that participants displayed visuomotor adaptation both Per Exposure, and Pre-/Post-Exposure to altered VF (VF condition*Time: p < 0.001). Per Exposure analyses revealed that CRPS participants tended to adapt their Movement Length to a lesser extent than pain-free participants (Group*VF condition: p = 0.048). Pre-/Post-Exposure analyses revealed that CRPS participants consistently performed larger movements than pain-free participants (p = 0.002). Both groups performed similarly for the Limb Position Sense task, but CRPS participants displayed significantly larger errors for Movement Accuracy, suggesting impaired proprioceptive integration in the CRPS group.DiscussionThese findings support the idea that visuomotor adaptation is preserved in CRPS and can be used to promote movement.